The understanding of the Islamic banking concept among Muslim community in Malaysia. - Awang, Mohd Daud; Jusoh, Mohd Kamal Azman; Borhan, Joni Tamkin; Wan Musa, Wan Salehaton
As we know, Malaysia had introduced Islamic Banking System (IBS), with the establishment of Bank Islam Malaysia Berhad (BIMB). The main factor of success is the collective efforts of all Muslims in avoiding "riba", a common practice in conventional banking system. Although IBS has offered more than 20 years of modem banking services, many Muslims community have expressed their lack of understandings of the Islamic banking concepts. The study is to explore how much the Muslim society in Malaysia understands IBS. This paperwork aims to measure the level of understanding among Muslim in the East Coast of Malaysia. Based on the survey analysis, the researcher finds the low level of understanding about IBS. Therefore, this paperwork will give some suggestions on how to increase the level of awareness among community especially Muslim towards IBS. The researcher believes that the government's inspiration of IBS's growth to 20% in national banking system by 2020 will succeed through consistent efforts in promoting IBS.